A C-Terminally Truncated Variant of Neurospora crassa VDAC Assembles Into a Partially Functional Form in the Mitochondrial Outer Membrane and Forms Multimers in vitro - Ferens, Fraser G.; Summers, William A. T.; Bharaj, Ameet; Stetefeld, Jörg; Court, Deborah A. (Frontiers in Physiology, 2021)
The voltage-dependent anion-selective channel, VDAC, is a porin in the mitochondrial outer membrane (MOM). Unlike bacterial porins, several mitochondrial beta-barrels comprise an odd number of beta-strands, as is the case for the 19 beta-stranded VDAC. Previously, a variant of VDAC from Neurospora crassa, VDAC-deltaC, lacking the predicted 19th beta-strand, was found to form gated, anion-selective channels in artificial membranes. In vivo, the two C-terminal beta-strands (beta18 and beta19) in VDAC from a beta-hairpin necessary for import from the cytoplasm into mitochondria, and the beta-signal required for assembly in the mitochondrial outer membrane resides in beta19. The current study demonstrates that the putative 18-stranded beta-barrel formed by VDAC-deltaC can be imported and assembled in the MOM in vivo and it partially rescues the phenotype associated with deletion of VDAC from a strain of N. crassa. When expressed and purified from E. coli, VDAC-deltaC can be folded into a beta-strand-rich form in decyl-maltoside. Size exclusion chromatography (SEC) alone or combined with multi-angle light scattering (SEC-MALS) and analytical ultracentrifugation revealed that, unlike full-length VDAC, VDAC-deltaC can self-organize into dimers and higher order oligomers in the absence of sterol.